Heartbeat Anomaly Detection Method Based on Electrocardiogram using Improved Certainty Cognitive Map - Sumiati, . (2023)
Diagnosing heart defects is generally done through the Certainty Factor (CF) approach and the Cognitive Map (CM) approach. The first problem is the lack of the Certainty Factor method, the CF value has not shown a semantic relationship between one evidence and another, so that it forms a complete rule and shows the degree of confidence with a clear map of evidence. The second problem lies in the weakness of CM, namely cognitive maps do not model certainty in variables but only form deductive reasoning. This research was conducted using the Certainty Cognitive Map (CCM) approach used to diagnose heart disorders based on electrocardiogram data. This research has 3 objectives To develop algorithms for detecting heart conditions as either abnormal or normal using the modified cognitive map (CM) approach, To develop detection algorithms for anomalous heart conditions based on the enhancement of Certainty Factor (CF) technique, and To evaluate and validate the effectiveness of the new proposed model specifically the Certainty Cognitive Map (CCM) for identifying heart defects. The results of this test were carried out using the Mean Squared Error (MSE) and Root Mean Squared Error (RMSE) approaches. Based on the results CF Method gave a Mean Squared Error (MSE) of 0.24 and Root Mean Squared Error (RMSE) of 0.48. The results of testing the CM Method gave a Mean Squared Error (MSE) of 0.80 and Root Mean Squared Error (RMSE) of 0.89, the results of testing the MCF Method with a Mean Squared Error (MSE) of 0.79 and gave Root Mean Squared Error (RMSE) of 0.89. The test results of the MCM Method gave a Mean Squared Error (MSE) of 0.65 and Root Mean Squared Error (RMSE) of 0.80 and the test results of the CCM Method with a Mean Squared Error (MSE) of 0.15 and a Root Mean Squared Error (RMSE) of 0.39. So the CCM method which is a modification of CF and modification of CM provides a better level of accuracy in diagnosing heart defects as compared to the CF method and the CM method.